Fragile Resilience: A Macro-Micro Analysis of Post Pandemic Economic Recovery and Multidimensional Poverty in Nepal - Khatiwada, Padma Prasad (Journal of Research and Development, 2026)
Despite a rebound in GDP growth to projected levels of 4.6% in FY 2024/25, Nepal’s economic recovery remains structurally fragile, characterized by a "debt-welfare" divergence. While aggregate indicators suggest stabilization, the translation of growth into poverty reduction has stalled due to inflationary pressures and reliance on remittance income (~26% of GDP). This study evaluates the elasticity of poverty reduction relative to economic growth in the post-federalism era. It aims to contrast national macro-trends with micro-level deprivations in rural governance units. A mixed methods approach was employed. Macro-level analysis utilized the Fourth Nepal Living Standards Survey (NLSS-IV 2023/24) and Economic Survey 2024/25 data. At the micro-level, a stratified cluster random survey of 963 households was conducted across three districts (Dang, Kapilvastu, Nawalpur) to assess rights-based access to services. National data reveals a poverty headcount of 20.27%, with a stark rural-urban divide (24.7% vs. 18.3%). While the Multidimensional Poverty Index (MPI) has declined to 17.4%, deprivation intensity remains high in nutrition and schooling. Preliminary micro-evidence suggests that federal restructuring has not yet optimized service delivery, with marginalized caste groups (Dalits) lagging significantly in Human Development Index (HDI) metrics. Economic growth in Nepal is becoming less "pro poor." The graduation from LDC status faces headwinds from low domestic productivity and high vulnerability to climate and external shocks. Interventions must shift from broad-based fiscal expansion to targeted social protection floors and the digitization of service delivery to bypass structural governance bottlenecks.